State Power and Asylum Seekers in Ireland An Historically Grounded Examination of Contemporary Trends - Loyal, Steven (Springer International Publishing, 2018)
'Readers will benefit hugely from this original and timely sociological analysis of nation states' responses to asylum seekers. Loyal and Quilley provide a socio-historical awareness that is often missing from public debate. Focusing on the case of Ireland, they develop a sophisticated analytical framework of broader significance. A much-needed book that deserves to be widely discussed within and beyond academia.' -Rubén Flores, Assistant Professor of Sociology, Higher School of Economics, Russia 'Migration is an emotive and politically explosive topic, but Loyal and Quilley stand back and detachedly set it in historical and global context. They focus especially on Ireland, which went abruptly from nearly two centuries of being a land from which people emigrated to being one to which they immigrated in substantial numbers. This makes for a fascinating case study of international interest.' -Stephen Mennell, Professor Emeritus of Sociology, University College Dublin, Ireland Detailing the reception, treatment and sometimes, eventual deportation, of asylum seekers in Ireland, Loyal and Quilley discuss contemporary immigration issues in light of the overall social, historical, and economic development of Irish society and state immigration policy. State Power and Asylum Seekers in Ireland will interest scholars and students of historical sociology, sociological theory and social policy, political sociology, migration and the psycho-social experience of asylum seekers. Steven Loyal is Associate Professor in the School of Sociology at University College Dublin, Ireland. Stephen Quilley is Associate Professor of Social and Ecological Innovation at the University of Waterloo, Canada.